INNOVATION MINDSET MODEL AT THE EARLY STAGE STARTUP WITH BERKELEY INNOVATION INDEX APPROACHED - Sarika Fitri; Asri Pertiwi (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Digital startups play an important role in the growth of nation’s economy, but many startups fail within their first year due to lack of any new ideas. This paper concentrates to modelling innovation mindset of founder to answer how can innovation mindset of founders be able to influence the propensity to innovate and what factors of which innovation mindset at need to be possed by the founders to encourage personal innovation. In this research, the presenting data and the method used is descriptive qualitative. The unit analysis of this study were startups digital with minimum running at validation phase, early stage and bootstrapping criteria and the informants were Top Management Team (TMT) level known as founder or cofounder who convey optimism and consistently manage the resources for innovation that will lead to successful innovation. Data were collected by triangulation technique which is Berkeley Innovation Index (BII) questionnaire to measure innovation mindset index with 6 constructsTrust; Believe; Resilience; Perfection; Diversity; Collaboration. Then, conduct a quick response statement, and the last is interview based on BII constructs. The result of this research produced the personality traits model, this model overview of how to get higher propensity to innovate at the early stage digital startup. As a conclusion from the model it delivered 4 propositions about the propensity to innovate by individuals.